Oxytetracycline inhibition of mitochondrial protein synthesis in bovine lymphocytes infected with Theileria parva or stimulated by mitogen - Spooner, P.R. (Cambridge University Press, 1990)
Oxytetracycline (OTC) significantly inhibited cytochrome c oxidase activity in bovine lymphocytes infected withTheileria parvaand in uninfected mitogen-stimulated lymphocytes. The inhibitory effect was detectedin vitrowithin 24 h of treatment with drug concentrations as low as 1 µg/ml. Following mitogen stimulation of lymphocytes, concentrations of 3 and 10 µg/ml OTC completely inhibited an increase in cytochrome c oxidase activity for 48–72 h. This inhibitory activity was considered to be due to a direct effect on lymphoblast mitochondrial protein synthesis. As a consequence, adenosine triphosphate activity was significantly reduced in lymphocytes stimulated either by infection withT. parvasporozoites or by mitogen and then treated with OTC. The results also indicated that parasite mitochondrial protein synthesis was inhibited by OTC. The activity of OTC reported in this study could explain the suppression of disease following ‘infection and treatment’ immunization against East Coast fever and thein vitrodrug-inhibition of schizont development.